Feed-forward algorithms for time-optimal settling of hard disk drive servo systems - Yuhong Huang; Messner, W.C.; Steele, J. (Proceedings of the IECON '97 : 23rd International Conference on Industrial Electronics, Control, and Instrumentation, 1997)
This paper presents novel time-optimal feedforward algorithms for a disk drive servo system with rotary actuator. The proposed method specifically minimizes the settling time of the servo positioning systems by applying an appropriate feedforward signal at seek-track hand off in the presence of bias disturbances. Two feedforward schemes have been investigated in the paper. They are the constant feedforward scheme and the exponential feedforward scheme. It is shown that while the former yields minimum settling time, the latter gives better robustness of the system performance when the estimation of the bias disturbance is subject to statistical errors. The proposed control schemes have been implemented on a test stand with a 3.5" hard disk drive. Using the proposed scheme, seek time has been improved by as much as 38% for short seeks and 54% for long seeks. Both simulation and experimental results are shown. The proposed algorithms are simple and can be easily integrated with the existing disk drive servo control systems. The stability of the servo system been augmented will not be affected.